2023
DOI: 10.3390/genes14071311
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between TLR3 rs3775291 Polymorphism and Infectious Diseases: A Meta-Analysis of Case-Control Studies

Abstract: As the host’s first line of defense against pathogens, Toll-like receptors (TLRs), such as the TLR3, are genes encoding transmembrane receptors of the same name. Depending on their expression, TLRs cause a pro- or anti-inflammatory response. The purpose of the article was to determine whether there is an association between the Toll-like receptor 3 (TLR3) rs3775291 Single Nucleotide Polymorphism—SNP and susceptibility to infections. This review was conducted according to the Preferred Reporting Items for Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…The frequency of the mutant allele (T) of SNP rs3775291 previously reported by several studies registered at the National Center for Biotechnology Information (NCBI) in Latin American populations was very different from that found in the present research in a cohort of the Amazonian population in Brazil. The Latin American frequency of the presence of this SNP mutant allele varies between 0 and 28%, while in the cohort of this study, only approximately 2% of the (T) allele was found (National Center of Biotechnology Information, 2023b; Silva et al, 2023b). This distribution of alleles related to the genotyping of this SNP in the Amazonian cohort was different even in relation to other research published in other Brazilian regions (Santos et al, 2019;Singh and Samani, 2022).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The frequency of the mutant allele (T) of SNP rs3775291 previously reported by several studies registered at the National Center for Biotechnology Information (NCBI) in Latin American populations was very different from that found in the present research in a cohort of the Amazonian population in Brazil. The Latin American frequency of the presence of this SNP mutant allele varies between 0 and 28%, while in the cohort of this study, only approximately 2% of the (T) allele was found (National Center of Biotechnology Information, 2023b; Silva et al, 2023b). This distribution of alleles related to the genotyping of this SNP in the Amazonian cohort was different even in relation to other research published in other Brazilian regions (Santos et al, 2019;Singh and Samani, 2022).…”
Section: Discussioncontrasting
confidence: 87%
“…Regarding the literary scenario on associations between the investigated TLR3 SNPs and infections, several studies have already linked the rs3775291 SNP with infectious diseases ( Lee et al., 2013 ; Chen et al., 2017b ; Santos et al., 2019 ; Posadas-Mondragón et al., 2020 ; Redondo et al., 2022a ). A recent meta-analysis by ( Silva et al, 2023a ; Silva et al, 2023b ) summarized data found by primary research in several countries involving this SNP and infectious diseases. As a result, the authors found that the mutant allele (T) was linked to a 0.16-fold increased risk of virus infection worldwide ( Silva et al., 2023b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cochrane Chi-Square test and the I-square measure (I 2 ) were used to determine the considerable statistical difference ( p ≤ 0.05 was considered a significant threshold) [ 19 ]. The correlation test for Begg and a funnel plot were used to examine the potential for publication bias ( p ≤ 0.05 was considered statistically significant) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…TLRs play a key role in generating and maintaining the innate immune response, in addition to guiding the adaptive immune response in infections. Therefore, SNPs in these genes can generate different levels of receptor expression, generating uncoordinated immune responses through excessive or reduced cytokine production [21][22][23].…”
Section: Introductionmentioning
confidence: 99%